If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (w + 4)(w + 5) = 12 Reorder the terms: (4 + w)(w + 5) = 12 Reorder the terms: (4 + w)(5 + w) = 12 Multiply (4 + w) * (5 + w) (4(5 + w) + w(5 + w)) = 12 ((5 * 4 + w * 4) + w(5 + w)) = 12 ((20 + 4w) + w(5 + w)) = 12 (20 + 4w + (5 * w + w * w)) = 12 (20 + 4w + (5w + w2)) = 12 Combine like terms: 4w + 5w = 9w (20 + 9w + w2) = 12 Solving 20 + 9w + w2 = 12 Solving for variable 'w'. Reorder the terms: 20 + -12 + 9w + w2 = 12 + -12 Combine like terms: 20 + -12 = 8 8 + 9w + w2 = 12 + -12 Combine like terms: 12 + -12 = 0 8 + 9w + w2 = 0 Factor a trinomial. (8 + w)(1 + w) = 0Subproblem 1
Set the factor '(8 + w)' equal to zero and attempt to solve: Simplifying 8 + w = 0 Solving 8 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + w = 0 + -8 Combine like terms: 8 + -8 = 0 0 + w = 0 + -8 w = 0 + -8 Combine like terms: 0 + -8 = -8 w = -8 Simplifying w = -8Subproblem 2
Set the factor '(1 + w)' equal to zero and attempt to solve: Simplifying 1 + w = 0 Solving 1 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + w = 0 + -1 w = 0 + -1 Combine like terms: 0 + -1 = -1 w = -1 Simplifying w = -1Solution
w = {-8, -1}
| 3=1/2(3x-6) | | 6z-z=-2+3z-3-1 | | 1/3(0)-1/4y=2 | | 10x-12=-2x+12 | | 3(2x+1)+3x=6x+3 | | 12=1/3(4x-3) | | 8(m+2)= | | 112000=-40x^2+4400x | | 6-13x+6x^2=0 | | 5(4x-1)-9x=50 | | p(x)=-40x^2+4400x | | f(x)=x(3x+4)+3 | | 429/x=21/100 | | 4(2n-5)/3=20 | | 1.5q=-6.8 | | 20+6n=150-4n | | 5p+11+7p=107 | | 5g-16=g(4g-4) | | -p(3p+5)= | | -1+2x=-4x+23x | | 6x(6x+3)=48 | | 8x=67 | | 32+20x= | | 10=5v-3v | | x^7y^9/y^2 | | 8x-4x+5=3 | | 420=12X*X | | -4(2f+11)=44 | | y^-9/y^-3 | | -8k(2-d)= | | 4-a=4 | | -108+11x=-x+132 |